2021
DOI: 10.3389/fimmu.2021.738962
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Recurrent Pregnancy Loss: A Mysterious Compass?

Abstract: Recurrent pregnancy loss (RPL) is a common and severe pathological pregnancy, whose pathogenesis is not fully understood. With the development of epigenetics, the study of DNA methylation, provides a new perspective on the pathogenesis and therapy of RPL. The abnormal DNA methylation of imprinted genes, placenta-specific genes, immune-related genes and sperm DNA may, directly or indirectly, affect embryo implantation, growth and development, leading to the occurrence of RPL. In addition, the unique immune tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 198 publications
(249 reference statements)
0
17
0
Order By: Relevance
“…During the regulation of epigenetic modification processes, DNA methylation and histone modification interact with each other. DNA methylation is the earliest and most extensively studied epigenetic modification, which takes the CpG island as the central link (Zhou et al, 2021). Recent studies have indicated that methylation of CpG islands is related to the methylation status of H3K4 (Zardo, 2021), and the levels of methylated H3K4 (H3K4me3) tend to be inversely correlated with DNA methylation (Okitsu Cindy and Hsieh, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the regulation of epigenetic modification processes, DNA methylation and histone modification interact with each other. DNA methylation is the earliest and most extensively studied epigenetic modification, which takes the CpG island as the central link (Zhou et al, 2021). Recent studies have indicated that methylation of CpG islands is related to the methylation status of H3K4 (Zardo, 2021), and the levels of methylated H3K4 (H3K4me3) tend to be inversely correlated with DNA methylation (Okitsu Cindy and Hsieh, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that methylation of CpG islands is related to the methylation status of H3K4 (Zardo, 2021), and the levels of methylated H3K4 (H3K4me3) tend to be inversely correlated with DNA methylation (Okitsu Cindy and Hsieh, 2007). DNA methylation is mainly established and maintained by DNA methyltransferases (DNMTs) that transfer a methyl group from S-adenyl methionine (SAM) to the fifth carbon of a cytosine residue to form 5mC (Zhou et al, 2021) (Chen and Zhang, 2020), while the active removal of methylation marks relies on the activity of ten-eleven translocation (TET) enzymes and thymine DNA glycosylase (TDG) (Parry et al, 2021). After fertilization, including the deletion of most methylation marks inherited from the gametes and the subsequent establishment of the embryonic methylation pattern, they show dynamic changes during development (Zeng and Chen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The most pivotal epigenetic modifications are DNA methylation, histone modifications and nucleosome remodeling. The current epigenetic studies investigating RPL mainly focus on DNA methylation ( 15 ). The main methods of DNA methylation analyses are bisulfite sequencing, array or bead hybridization, pyrosequencing, methylation-specific polymerase chain reaction (PCR), high -performance liquid chromatography-ultraviolet, and mass spectrometry (MS)-based approaches ( 16 ).…”
Section: Overview Of Omicsmentioning
confidence: 99%
“…DNA methylation has been shown to play a key role in regulating genes involved in metabolic adaptation during pregnancy, and aberrant DNA methylation has been demonstrated during pregnancy complications such as preeclampsia, hypertension, GDM, early pregnancy loss and preterm birth (24)(25)(26)(27). Moreover, altered DNA methylation patterns have been observed in the placenta and cord blood of women with GDM, and have been identified as potential factors that mediate in utero fetal programming (26,(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%